Защита силовых установок танков от поражения с верхней полусферы - Климов, В. Ф.; Глебов, В. В.; Колбасов, А. Н.; Михайлов, В. В.; Шипулин, А. А. (НТУ "ХПИ", 2017)
У статті проведено аналіз рівня захисту танків від ураження силових установок танків та приведені основні напрямки поліпшення захисту силових установок з верхньої напівсфери.

The article analyzes the level of protection of tank power packs against defeat and lists the main trends in improvement of power pack protection in the upper semisphere.
Protection of tank power packs against defeat in the top projection
Keywords: эжекционная система охлаждения; система воздухопитания; теплообменники; воздухоочиститель